Developing Jumping in Volleyball Players of Different Ages and Preparations - Usmanov Shohrukh Khojamurodovich; Kamolov Siyavush Said ugli (International Journal on Orange Technologies, 2022)
The article identifies the means of rapid and effective formation of this ability based on the study of movement games, types of jumps typical of modern volleyball through various exercises, the kinematic factors that provide jumping and jump endurance.